Deep brain stimulation: a new treatment for hypertension? - Green, A; Wang, S; Bittar, R; Owen, S; Paterson, D; Stein, J; Bain, P; Shlugman, D; Aziz, T (2007)
We report a 61-year-old hypertensive man who underwent deep brain stimulation of the periventricular/periaqueductal grey area for the relief of chronic neuropathic pain affecting his oral cavity and soft palate. During intraoperative stimulation, we were able to modulate his blood pressure up or down, depending on electrode location. This is the first evidence that hypertension could be effectively treated with electrical stimulation of the midbrain.